Vascular effects of hydrogen sulphide - influence of O2 - Erfaida, Yousef (2020)
Hydrogen sulphide (H2S), a toxic gas, has recently been shown to be generated endogenously by biological tissue and it has emerged as a novel and important biological mediator in the vascular system. In blood vessels, H2S has been shown to produce complex actions, including both vasorelaxation and vasoconstriction, through different mechanisms, depending on vessel origin and oxygen levels. This thesis examined the effects of H2S on blood vessels and examined the influence of oxygen concentration on vascular responsiveness and the mechanisms involved. This study also investigated whether H2S contributed to the hypoxic vascular response. Porcine splenic and pulmonary vessels and human chorionic blood vessels were set up in an isometric tension recording system, blood vessels were pre-contracted and responses to the H2S donor, NaHS, were produced in the presence and absence inhibitors, under 95% O2:5% CO2, 95% Air: 5% CO2 and 95% N2:5% CO2 gassing conditions. Western blot analysis was carried out to determine Cystathionine β synthase (CBS) and Cystathionine γ lyase (CSE) expression in porcine splenic and pulmonary arteries.